2020
DOI: 10.1109/tns.2020.2977698
|View full text |Cite
|
Sign up to set email alerts
|

Inherent Uncertainty in the Determination of Multiple Event Cross Sections in Radiation Tests

Abstract: In radiation tests on SRAMs or FPGAs, two or more independent bitflips can be misled with a multiple event if they accidentally occur in neighbor cells. In the past, different tests such as the "birthday statistics" have been proposed to estimate the accuracy of the experimental results. In this paper, simple formulae are proposed to determine the expected number of false 2-bit and 3-bit MCUs from the number of bitflips, memory size and the method used to search multiple events. These expressions are validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…N BF being the number of bitflips, W the data wordwidth, and L N the memory size in bits. The inner term inside the exponential function is just the expected number of false 2-bit MBUs and a similar expression can be used to determine the number of false 3-bit ones [17], [18]. The rightwards columns in Table II show the expected number of false MBUs as well as the probability of occurring at least a false MBU of any multiplicity with W = 32, L N = N ′ CF .…”
Section: B Extraction Of Multiple Events: Mbusmentioning
confidence: 99%
See 1 more Smart Citation
“…N BF being the number of bitflips, W the data wordwidth, and L N the memory size in bits. The inner term inside the exponential function is just the expected number of false 2-bit MBUs and a similar expression can be used to determine the number of false 3-bit ones [17], [18]. The rightwards columns in Table II show the expected number of false MBUs as well as the probability of occurring at least a false MBU of any multiplicity with W = 32, L N = N ′ CF .…”
Section: B Extraction Of Multiple Events: Mbusmentioning
confidence: 99%
“…It is important, in any case, to determine if these events are actual or false, due to the random occurrence of bitflips in neighbor cells. In [18], it has been proposed that the average number of false 2-bit MCUs for this technique is m R · N BF · (N BF − 1) /L N , m R being the number of critical DV distances used to relate pairs of addresses. In the worst case (TM5), this number is only 0.13, much lower than the actual value for this test (105).…”
Section: Extraction Of Multiple Events: Mcusmentioning
confidence: 99%
“…Since there seems to be a correlation between the total number of bitflips in a round of reading and the appearance of these particular MCUs, it was suspected that some (or maybe all) of these events were a consequence of independent SBUs that coincidentally affected close SRAM bitcells and therefore, they were erroneously considered as part of the same multiple event. In previous works [23], [24], the authors studied that the probability of observing so-called "false" multiple events becomes non negligible if the number of bitflips that occurred in the same round of reading is high enough. In particular, if Manhattan distance is used as the metric to group bitflips into the same MCU, it was postulated that the expected number of false 2-bit MCUs is:…”
Section: Discussion Of False Multiple Eventsmentioning
confidence: 99%
“…Where N BF is the number of bitflips occurred in the experiment, M D is the threshold value of the Manhattan distance used and L N is the size of the memory in bits. This equation was developed by exploiting the idea that a given SBU has a so-called "area of influence" that is defined as the number of bitcells existing around it at a Manhattan distance lower or equal to M D. In [24], it was demonstrated that it can be obtained as:…”
Section: Discussion Of False Multiple Eventsmentioning
confidence: 99%
See 1 more Smart Citation